Rwandan Genocide Conflict Represented in the Novel “Led by Faith” (Hiski Malang, 2020)
This study discusses the ethnic conflict in the Rwandan genocide in the novel Led by Faith: Rising from The Ashes of Rwandan Genocide written by Immaculée Ilibagiza. The novel is set in Rwanda, the country that was known as the place of the fastest killing in the world history, within 100 days killed more than 800.000 people. This novel is based on the author’s experience in surviving from the Rwandan genocide. Therefore, it is interesting to discuss how the author represented the genocide in the novel. This study applied conflict theory by Dahrendorf which focus on four aspect: Two aspects of society (conflict and consensus), power and authority, the groups involved in the conflict, and conflict and social change. The data are taken from the novel Led by Faith by using descriptive analysis techniques. The study reveals that the conflict between Hutu and Tutsi ethnics was represented as the power dynamics among the authorities. The conflict influenced the social change and social structure of the Rwandan society.